Testing practitioner handbook : gain insights into the latest technology and business trends within testing domains - Rajani, Renu (Packt Publishing, 2017)
Gain insights into the latest technology and business trends within testing domains About This Book This book covers the latest trends that every Testing and QA professional should keep up-to-date with given the advancements in digital technologies. Master cutting-edge testing techniques for emerging areas such as IOT, Machine Learning, Cognitive. Best practices for Testing and Quality Assurance within several industry domains. Who This Book Is For This book is targeted at those working in the QA and Testing areas. The book does not cover testing basics, which QA professional are already familiar with - for example, writing a test plan or test case, and so on. What You Will Learn Understand the TCOE model, managed services, the structure of testing in Agile/DevOps engagements, factory models, and crowdsourcing Implement testing processes, practices, and automation tools in the Agile/DevOps life cycle Adapt to current technologies in social media, mobile, analytics and the Cloud Leverage cognitive intelligence/machine-learning, robotics, and the Internet of Things in testing How key industries/domains (consumer products and retail, energy and utilities, healthcare, telecom, and automotive) adapt to digital transformation Future directions for the QA industry, consulting careers, testing profession, and professionals In Detail The book is based on the author`s experience in leading and transforming large test engagements and architecting solutions for customer testing requirements/bids/problem areas. It targets the testing practitioner population and provides them with a single go-to place to find perspectives, practices, trends, tools, and solutions to test applications as they face the evolving digital world. This book is divided into five parts where each part explores different aspects of testing in the real world. The first module explains the various testing engagement models. You will then learn how to efficiently test code in different life cycles. The book discusses the different aspects of Quality Analysis consideration while testing social media, mobile, analytics, and the Cloud. In the last module, you will learn about futuristic technologies to test software. By the end of the book, you will understand the latest business and IT trends in digital transformation and learn the best practices to adopt for business assurance. Style and approach This book is a compilation of the latest business and IT trends in digital transformation & T...